2020
DOI: 10.1021/acs.macromol.0c01321
|View full text |Cite
|
Sign up to set email alerts
|

Gas Transport in a Polymer of Intrinsic Microporosity (PIM-1) Substituted with Pseudo-Ionic Liquid Tetrazole-Type Structures

Abstract: We report a side group modification strategy to tailor the structure of a polymer of intrinsic microporosity (PIM-1). PIM-1 with an average of ∼50% of the repeat units converted to tetrazole is prepared, and a subsequent reaction then introduces three types of pseudo-ionic liquid tetrazole-like structures (PIM-1-IL x ). The presence of pseudo-ionic liquid functional groups in the PIM-1 structure increases gas selectivities for O 2 /N 2 and CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 77 publications
4
33
0
Order By: Relevance
“…Pseudo-PILs from post-functionalized PIM-1 were prepared by reacting tetrazole-modified PIM-1 with amines in the presence of MeOH to activate anionic sites in the polymer and introduce amines as anions and bearing a methylammonium, diisopropylamonium, and N , N -diisopropylethylamonium cation [ 123 ]. With increasing cation size, the BET surface area and the gas permeability progressively decreased, while the selectivity increased, maintaining values close to the 2008 upper bound for the CO 2 /N 2 gas pair (selectivity 35.5 at a CO 2 permeability of 817 Barrer) and the O 2 /N 2 gas pair (selectivity 4.5 at an O 2 permeability of 102 Barrer) for the N , N -diisopropylethylamonium cation.…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
See 3 more Smart Citations
“…Pseudo-PILs from post-functionalized PIM-1 were prepared by reacting tetrazole-modified PIM-1 with amines in the presence of MeOH to activate anionic sites in the polymer and introduce amines as anions and bearing a methylammonium, diisopropylamonium, and N , N -diisopropylethylamonium cation [ 123 ]. With increasing cation size, the BET surface area and the gas permeability progressively decreased, while the selectivity increased, maintaining values close to the 2008 upper bound for the CO 2 /N 2 gas pair (selectivity 35.5 at a CO 2 permeability of 817 Barrer) and the O 2 /N 2 gas pair (selectivity 4.5 at an O 2 permeability of 102 Barrer) for the N , N -diisopropylethylamonium cation.…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
“…Only small amounts were added, which were not able to form a gel, but in the case of [BMIM] 2 [Co(NCS) 4 ] it effectively increased the O 2 /N 2 selectivity from 3.77 for pure PIM-1 to 5.3 for the membrane with 2% of the cobalt complex. In an alternative approach, Guiver et al covalently connected the ionic liquid-like tetrazole-type structures as lateral substituents to the PIM-1 backbone [ 123 ], resulting in a PIL.…”
Section: Polymer/il Blends; Ion Gelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other types of functional groups that have been recently introduced into PIM structures include ionic liquids (ILs) and sulfonyl groups. [ 130,131 ] Guiver et al (2020) reported a number PIMs containing pseudo‐IL tetrazole‐like functional groups (PIM–1–IL x ) through side‐group modification of PIM‐1. [ 130 ] The gas permeation properties of IL‐modified PIMs approached the 2008 Robeson upper bounds with improved O 2 /N 2 and CO 2 /N 2 pure‐gas selectivities, coupled with lower pure‐gas permeabilities when compared with the original PIM‐1.…”
Section: Development Of Novel Pim Materialsmentioning
confidence: 99%